THE INNER CONFLICT OF THE CHARACTER LALA IN THE FILM POSESIF BY EDWIN: A PSYCHOLOGICAL STUDY - Salsabila Sabililah, Cantika Safa; Fauzan, Akhmad; Pamungkas, Onok Yayang; Mulasih (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2026)
Abstract This study analyses the psychological conflict of the character Lala in Edwin’s film Posesif (2017) using Carl Gustav Jung’s analytical psychology framework, concentrating on three psychic layers: consciousness and ego, personal unconscious and complexes, and collective unconscious and archetypes. The urgency of this research lies in the scarcity of Jungian analytical psychology studies addressing the representation of possessive relationships in contemporary Indonesian cinema. Employing a qualitative method with a literary psychology approach, data were collected through observation and note-taking techniques applied to dialogues, scenes, character expressions, and other audiovisual elements and subsequently analysed through descriptive-qualitative procedures comprising data reduction, data presentation, and conclusion drawing. The findings reveal that Lala experiences inner conflict manifested as anxiety, affective ambivalence, and self-identity disintegration in response to the possessive relationship she endures, with approach-avoidance conflict emerging as the dominant pattern obstructing her individuation process. These findings contribute theoretically by demonstrating the relevance of Jungian complex and archetype concepts in reading the psychological dynamics of female characters within Indonesian film narratives while simultaneously broadening the scope of literary psychology studies to encompass audiovisual media. Keywords: analytical psychology; Carl Gustav Jung; inner conflict; possessive relationship